Developing “Transportastic” Learning Application to Enhance Vocabulary Mastery for Young Learners - Wardhani, Dhea Siwy; Sari, Ike Dian Puspita (Verba: Journal of Applied Linguistics, 2024)
Speakers of different languages are taught English as a Foreign Language (EFL) all over the world, including in Indonesia. English is taught to children from a young age. Today’s technology is thought to help humans do tasks quickly and effectively because of how quickly it is developing. This research aims to know how is Transportastic application developed for young learners. This research used a research and development (R&D) design. The research procedures are: (1) the researcher examined the requirement for creating educational resources for kindergarten students, (2) the researcher gathered files that would need to be added to the program, including images and audio, (3) the Transportastic application was designed based on the observation found in the syllabus and the materials gathered, (4) the application was validated in front of expert validators, (5) the researcher finalized changes or revisions to the Transportastic application based on the expert validator’s validation checklist result, (6) the completed product, the Transportastic application, was designed and developed according to the revisions from the experts. This research shows that based on validation from expert, it was indicated that Transportastic application has been well designed for kindergarten level to learn vocabulary.